The Correlation between Mathematical Disposition and Problem Solving in Junior High School Students - Lomri, Yani Astika; Dasari, Dadan (Universitas Teknokrat Indonesia, 2024)
The aim of this study is to examine the relationship between mathematical disposition and problem-solving abilities of junior high school students. This research was conducted to understand the extent to which mathematical dispositions contribute to students' problem-solving abilities. The research method used in this study is a survey method with a cross-sectional design involving 25 seventh-grade students from the 2019/2020 academic year in a junior high school in Bandung city. Data on mathematical disposition were collected using a questionnaire, while problem-solving abilities were assessed using a disposition questionnaire instrument. Data analysis was conducted quantitatively using descriptive statistics (including mean, maximum value, minimum value, and standard deviation) and inferential statistics (using the product-moment correlation). The results of the study show that there is a positive correlation between mathematical disposition and students' problem solving abilities with a strong correlation level.